Experiences of patients undergoing hemodialysis treatment during the COVID-19 pandemic - Leonardo Silva da Costa; Ellen Cristina Barbosa dos Santos; Nelson Miguel Galindo Neto; Cynthia Roberta Dias Torres Silva; Guilherme Guarino de Moura Sá; Matheus Vinicius Barbosa da Silva; Juliana Lourenço de Araújo Veras (Universidade Federal do Ceará, 2024)
Objective: to reveal the experiences of patients undergoing hemodialysis treatment during the COVID-19 pandemic. Methods: this is a qualitative study conducted with 18 patients undergoing hemodialysis treatment, from the perspective of the Chronic Conditions Care Model. Data collection was performed through semi-structured interviews, the content was recorded and processed using the Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires software. Results: six classes emerged from the statements which addressed the following: challenges in building a new life routine; the fear of self-contagion and the family; mental suffering due to clinical vulnerability in facing the pandemic scenario; strategies for preventing COVID-19; the impacts of the immunization process against COVID-19; and the negative aspects of the experience of hemodialysis treatment during the pandemic. Conclusion: the experiences were permeated by challenges, especially in aspects related to mental health. Contributions to practice: this study provides an opportunity for applying targeted actions with a view to proposing contributions for planning nursing care aimed at patients undergoing hemodialysis treatment in possible future pandemic periods.